2020
DOI: 10.1080/03949370.2020.1789748
|View full text |Cite
|
Sign up to set email alerts
|

Male validation factor for three-spined stickleback (Gasterosteus aculeatus) mate choice likely evolutionarily conserved since 50 thousand years

Abstract: During mate choice, three-spined stickleback (Gasterosteus aculeatus) females make use of male olfactory cues to determine the suitability of potential mates in a species-and habitat-dependent manner. This signal contains peptides reflecting the individual male's MHC profile and a so-called male validation factor (MVF) indicating the species identity of the sender. In a two-armed flow channel, we exposed gravid females to male odour. The odours from males that produced only the MVF but no MHC signal yet were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Starting with Yamazaki et al [ 4 ] numerous studies, mostly with inbred strains of mice, showed that actual mate choice favors MHC dissimilar individuals e.g., [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. MHC-dependent mate choice was demonstrated also in other vertebrates such as rats [ 14 , 15 , 16 , 17 ], birds [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], fish [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], reptiles [ 38 ] small mammals [ 39 ], primates [ 40 ], and humans [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with Yamazaki et al [ 4 ] numerous studies, mostly with inbred strains of mice, showed that actual mate choice favors MHC dissimilar individuals e.g., [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. MHC-dependent mate choice was demonstrated also in other vertebrates such as rats [ 14 , 15 , 16 , 17 ], birds [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], fish [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], reptiles [ 38 ] small mammals [ 39 ], primates [ 40 ], and humans [ 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In part, this is because there has been suggested no plausible mechanism by which these genes, which code for cell-surface proteins, could also specify differential body odor’ [ 55 , 56 ]. A number of studies revealed mate choice that was based on odor, in rats [ 14 , 15 ], fish [ 29 , 30 , 31 , 32 , 33 , 34 , 36 ], reptiles [ 38 ], birds [ 24 , 25 , 26 ], small mammals [ 57 ], and Humans [ 42 , 43 , 44 , 45 , 46 , 58 ]. Thus, there must be a mechanism.…”
Section: Introductionmentioning
confidence: 99%